Frequency of Positive Findings on MRI of The Patients Diagnosed with Vertebral Metastases on Bone Scintigraphy - Zahra, Syeda Beenish; Ayesha Isani Majeed; Joveria Ehsan (Pakistan Armed Forces Medical Journal, 2024)
Objective: The present study is conducted with the aim to compare the bone scan and MRI findings for detecting spinal metastasis in our local population. Study design and duration: This cross sectional study was conducted at Radiology Department of Pakistan Institute of medical Sciences, Islamabad from May 2019-May 2020.Material and Methods: Total 30patients with confirmed diagnosis of cancer who were suspected for spinal metastasis on Tc-99m bone scan and sent for radiologic workup for confirm diagnosis of s            pine lesions were enrolled. MRI was performed on 1.5-tesla system using standard protocol. Spine was divided into four regions: cervical, thoracic, lumber and sacral regions. Region-wise bone metastasis were analyzed and compared for bone scan and MRI. Interpretations were considered concordant if both reports showed positive for metastatic lesions, while discordant if readings differ.Results: 63.3% of the study population were female. Mean age of the enrolled patients was 59.3±14.9 years. All the lesions of cervical region were concordant. Most of the discordance for MRI was noted for lumbar region, where 7 patients were reported as negative who were positive on bone scan. In case of bone scintigraphy, 2 patients were discordant for thoracic region who were positive on MRI.Conclusion: Very low discordance rate exists among MRI and bone scan. MRI is an effective imaging tool for detection of spinal metastasis with added benefits of no radiation dose to the patient and wider availability as compare to the bone scintigraphy.